2018
DOI: 10.1111/jopr.12995
|View full text |Cite
|
Sign up to set email alerts
|

Remake Rates for Single‐Unit Crowns in Clinical Practice: Findings from The National Dental Practice‐Based Research Network

Abstract: Purpose Some crowns returned from the laboratory are clinically unacceptable, and dentists must remake them. The objectives of this study were to: (1) quantify the remake rate of single‐unit crowns; and (2) identify factors significantly associated with crown remakes and intraoral fit. Materials and Methods Dentists participating in the National Dental Practice‐Based Research Network recruited patients needing crowns and documented fabrication techniques, patient characteristics, and outcomes. Crowns were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…The methods for this study have been previously reported . They are repeated here in part for the convenience of the reader, and expanded in sections that pertain specifically to this report.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods for this study have been previously reported . They are repeated here in part for the convenience of the reader, and expanded in sections that pertain specifically to this report.…”
Section: Methodsmentioning
confidence: 99%
“…Despite careful attention to detail and the use of current techniques and materials, dentists still must remake crowns that do not fit clinically; the remake rate approaches 4% . Such remakes require additional time and effort from the dentist, patient, and laboratory.…”
mentioning
confidence: 90%
“…Questions from the survey considered in this manuscript focused on techniques for making impressions, such as the use of different materials, retraction techniques, and tray types. Other questions from the survey focused on treatment recommendations, 55 material choices, and crown preparation techniques.…”
Section: Clinical Techniques Questionnaire Contentmentioning
confidence: 99%
“…1,2 The indications for crowns are diverse, and may include factors such as endodontic treatment, cracks and fractures of the tooth, large restorations, esthetic shortcomings, or significant caries. 1,3,4 When planning crowns, there is variation among dentists in…”
mentioning
confidence: 99%
“…3,4 In fact, evidence suggests recommendations for crowns may be influenced by factors unrelated to tooth and patient variables. 1 Dentists must make a variety of clinical decisions when fabricating crowns for their patients. Depending on the restorative material, historic guidelines suggest an optimal design for tooth preparation based on fundamental principles for predictable successful prosthodontic treatment.…”
mentioning
confidence: 99%